Tinjauan Pustaka Sistematis: Penanaman Sikap Nasionalisme melalui Kegiatan Upacara Bendera di Sekolah Dasar - Silviana Dinawati; Muhamad Taufik Hidayat (Universitas Negeri Padang, 2023)
This study analyzed the obstacles, strategies, and results of flag ceremony activities in Indonesian elementary schools. The method used in this study was a systematic literature review. The information used contained an attitude of nationalism. The literature review process was conducted by searching for relevant articles, evaluating them using data extraction, and then comparing the literature results. The database used was Google Scholar. The results of this study indicated that (1) the obstacles in cultivating nationalism are the lack of discipline, order, and mutual respect among people; (2) the strategies used in cultivating nationalism include reminding, guiding, and explaining, as well as involving teachers and students in instilling nationalism; (3) the result of cultivating nationalism in flag ceremony activities is the formation of individuals who are moral and ethical and understand the importance of the activities. The implications of this study were: first, teachers must be able to provide understanding and examples related to instilling nationalism; second, students can make habituation through good behaviour to be applied in daily life. This study revealed the inculcation of nationalism in Indonesian elementary schools comprehensively.